The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11403-018-0215-x
|View full text |Cite
|
Sign up to set email alerts
|

Are the stock and real estate markets integrated in China?

Abstract: This paper examines the dynamic short-run and long-run co-movement between the real estate and stock markets in China by employing a continuous wavelet method. We use gross domestic product and M2 (broad money supply) as control variables to eliminate the common factors of the two markets and to identify the real nexus between them. The empirical results show that the co-movement between real estate and stock prices is weak in the short run, except during the financial crisis period. Since the stock market is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Several studies have investigated the association between real estate and stock markets in the USA (Liow and Yang, 2005;Li et al, 2015;Hui and Chan, 2018;Zheng and Osmer, 2019), UK (Hui et al, 2011;Hui and Chan, 2013;Bouri et al, 2019), Germany (Gokmenoglu and Hesami, 2019); Greece (Gounopoulos et al, 2019), Australia (Lee et al, 2017), China (Zhang and Fung, 2006;Guo and Huang, 2010;Chan and Chang, 2014;Deng et al, 2017;Su et al, 2019), Taiwan (Chen, 2001;Liu and Chen, 2016) and Turkey (Yuksel, 2016;Bayraktar, 2019). However, to the best of our knowledge, no researcher has investigated the real estate and stock nexus in Pakistan.…”
Section: Integration Between Real Estate and Stock Markets 887mentioning
confidence: 99%
“…Several studies have investigated the association between real estate and stock markets in the USA (Liow and Yang, 2005;Li et al, 2015;Hui and Chan, 2018;Zheng and Osmer, 2019), UK (Hui et al, 2011;Hui and Chan, 2013;Bouri et al, 2019), Germany (Gokmenoglu and Hesami, 2019); Greece (Gounopoulos et al, 2019), Australia (Lee et al, 2017), China (Zhang and Fung, 2006;Guo and Huang, 2010;Chan and Chang, 2014;Deng et al, 2017;Su et al, 2019), Taiwan (Chen, 2001;Liu and Chen, 2016) and Turkey (Yuksel, 2016;Bayraktar, 2019). However, to the best of our knowledge, no researcher has investigated the real estate and stock nexus in Pakistan.…”
Section: Integration Between Real Estate and Stock Markets 887mentioning
confidence: 99%
“…Xu and Wang (2010) explored the correlation between real estate markets and cyclical fluctuations in the stock markets. This is also discussed by Yao and Song (2010), Lin and Tsai (2019), and Su, Yin, Chang, and Zhou (2019). Their conclusions conflict.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Their conclusions conflict. Some found that the stock markets influenced the real estate market (A. Li et al, 2014; Xu & Wang, 2010), while others found that the real estate market impacted the stock market (Lin & Tsai, 2019; Su et al, 2019). Other scholars discovered two‐way spillover effects between the two markets in China (Huang, 2014; Yao & Song, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though the methods of analysis were distinct, they both ended up with the same conclusion. In addition, Su et al [33] used a case study of China to reexamine this subject by including more factors in their analysis. In the long run, they discovered that changes in the price of real estate might have an effect on the price of shocks.…”
Section: Literature Reviewmentioning
confidence: 99%